Penerapan Resapan Biopori untuk Konservasi Lahan Desa Munggangsari Kab. Temanggung, Jawa Tengah - Muhammad Mukhlisin; Junaidi Junaidi (Politeknik Negeri Semarang, 2016)
Rapid urban growth resulting in rapid land-use changes will also result in reduced water absorption function and result in reduction of groundwater filling. Communities in Munggangsari Village are tobacco farmers and some of the sand miners in agricultural areas have resulted in the destruction of morphological and ecological systems of their lands that have the potential to cause disasters. In reducing the impact of that condition, Civil Engineering Department of Semarang State Polytechnic conduct devotion to community in the form of training and implementation in the form of training / workshop and counseling of land conservation and field practice aimed at raising awareness in terms of conservation and sustainability management of land resources and resources Ground water using simple Lubang Resapan Biopori (LRB) technology. This activity is expected to be done with good planning and measurable so as to maintain the conservation of water resources in the area.Kata Kunci : biopori, sistem drainase yang berkelanjutan, konservasi lahan.